Active Aging in the People’s Republic of China: A Case Study of Working After Retirement - CHRISTINA MAAGS; JINGWEN ZHANG (Asian Development Review, 2025)
This study examines trends in working after retirement and its relationship to the wider policy and welfare state context in the People’s Republic of China (PRC). Using a mixed methods approach, we first analyzed China Health and Retirement Longitudinal Study data for 2011–2020 to identify trends and individual- and household-level factors associated with working after retirement. We then examined how changes in the policy context shape older people’s economic participation over time, concluding with a discussion on the findings’ implications for the PRC’s social protection system. We argue that while mandatory retirement ages push certain older people out of the labor market, there is an increase in older people working beyond the retirement age, as opportunities to supplement pension income pull older people into the labor market. Yet, policymakers do not regulate this, pointing to a policy gap. Although an expanded labor force would reduce pressure on the PRC’s social protection system, it would also continue to reproduce preexisting socioeconomic inequalities.